A Review of Associations between Externalizing Behaviors and Prenatal Cannabis Exposure: Limitations & Future Directions - Ami S. Ikeda; Valerie S. Knopik; L. Cinnamon Bidwell; Stephanie H. Parade; Sherryl H. Goodman; Eugene K. Emory; Rohan H. C. Palmer (Toxics, 2022)
In utero cannabis exposure can disrupt fetal development and increase risk for various behavioral disruptions, including hyperactivity, inattention, delinquent behaviors, and later substance abuse, among others. This review summarizes the findings from contemporary investigations linking prenatal cannabis exposure to the development of psychopathology and identifies the limitations within the literature, which constrain our interpretations and generalizability. These limitations include a lack of genetic/familial control for confounding and limited data examining real world products, the full range of cannabinoids, and motives for use specifically in pregnant women. Taken together, our review reveals the need to continue to improve upon study designs in order to allow researchers to accurately draw conclusions about the development of behavioral consequences of prenatal cannabis exposure. Findings from such studies would inform policy and practices regarding cannabis use during pregnancy and move the field toward developing a comprehensive teratogenic profile of cannabis similar to what is characterized in the prenatal alcohol and tobacco literature.